Social Work for Sociologists : Theory and Practice / edited by Kate van Heugten, Anita Gibbs. - Heugten, Kate van (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015., 2017)
XI, 193 p. online resource.